State Failure' in provision of education and health services in Zimbabwe: Adjustments, adabtations and evolving coping stratergies of rural communities, 2000-2007. - Musekiwa, Norbert (Department of Political Studies, 2014)
The study is an analysis of how two rural communities in Zimbabwe adapted and responded to the decline in health and basic education services between 2000 and 2007. From 2000, Zimbabwe faced socioeconomic and political challenges that have been characterised as the "Zimbabwean crisis". The state became unable or unwilling to provide adequate education and health services to the majority of its citizens. The study sought to determine the nature and extent of the emerging coping strategies to a decline in the state service delivery. Hirschman‟s analysis of exit, voice and loyalty influenced the theoretical framework guiding the study. The reformulated framework incorporates three types of exit, three types of voice, three types of direct action, two types of loyalty, and other alternative options such as apathy and spiritualism. The methodological framework entailed a case study approach of two rural communities in Zimbabwe. The study purposely selected Maotsa and Shumba communities because of their individuality and diversity in terms of geography, socioeconomic conditions and the range of health and education services provided. Data gathering involved conducting semi-structured interviews and focus group discussions in the two communities between July 2007 and June 2008. The study employed the membership categorization device to analyse data from the interviews. The responses were also post coded and analysed with Statistical Package for Social Scientists version 16. The statistical analysis complemented the qualitative analysis. The study established that communities and individuals responded to the decline of public services through a multiple of strategies. The prominent responses included exit, voice, direct action and a sense of hopelessness and apathy all occurring in multiple variants. In the face of declining public services, the communities responded by going beyond the exercise of voice in the original Hirschman formation of complaining and protesting to collectively cooperating or individually acting to provide the public goods in place of those previously provided by the state. Unlike traditional voice in which consumers seek corrective action by others, Shumba and Maotsa community restored the public services through voluntary local contributions of labour, money and materials. Arising from previous failures at cooperative effort, the Shumba community was less successful at collective action. Due to increased poverty incidence, the alternative of producing public goods locally was not enduring and the communities invariably sought to leverage external donor support. Shumba community was more successful in attracting external support for community projects.